Integrated omics profiling reveals systemic dysregulation and potential biomarkers in the blood of patients with neuromyelitis optica spectrum disorders - Zuoquan Xie; Qinming Zhou; Jin Hu; Lu He; Huangyu Meng; Xiaoni Liu; Guangqiang Sun; Zhiyu Luo; Yuan Feng; Liang Li; Xingkun Chu; Chen Du; et al. (Journal of Translational Medicine)
Abstract Background Neuromyelitis optica spectrum disorders (NMOSD) are autoimmune conditions that affect the central nervous system. The contribution of peripheral abnormalities to the disease's pathogenesis is not well understood. Methods To investigate this, we employed a multi-omics approach analyzing blood samples from 52 NMOSD patients and 46 healthy controls (HC). This included mass cytometry, cytokine arrays, and targeted metabolomics. We then analyzed the peripheral changes of NMOSD, and features related to NMOSD's disease severity. Furthermore, an integrative analysis was conducted to identify the distinguishing characteristics of NMOSD from HC. Additionally, we unveiled the variations in peripheral features among different clinical subgroups within NMOSD. An independent cohort of 40 individuals with NMOSD was utilized to assess the serum levels of fibroblast activation protein alpha (FAP). Results Our analysis revealed a distinct peripheral immune and metabolic signature in NMOSD patients. This signature is characterized by an increase in monocytes and a decrease in regulatory T cells, dendritic cells, natural killer cells, and various T cell subsets. Additionally, we found elevated levels of inflammatory cytokines and reduced levels of tissue-repair cytokines. Metabolic changes were also evident, with higher levels of bile acids, lactates, triglycerides, and lower levels of dehydroepiandrosterone sulfate, homoarginine, octadecadienoic acid (FA[18:2]), and sphingolipids. We identified distinctive biomarkers differentiating NMOSD from HC and found blood factors correlating with disease severity. Among these, fibroblast activation protein alpha (FAP) was a notable marker of disease progression. Conclusions Our comprehensive blood profile analysis offers new insights into NMOSD pathophysiology, revealing significant peripheral immune and metabolic alterations. This work lays the groundwork for future biomarker identification and mechanistic studies in NMOSD, highlighting the potential of FAP as a marker of disease progression.